“Colégio das freiras”: educação feminina no curso normal no sul de Goiás (1939-1968) - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The present research has as object of study the feminine education within the Normal School Senator Hermenegildo Lopes de Morais, known as Nuns College, founded in the city of Morrinhos, South of Goiás, by the Congregation of the Augustinian Missionaries. To think female education in this institution, is adopted as the time frame period 1939-1968, which represents the start and end of the action of the Augustinian Missionary nuns ahead of this educational institution. It is assumed that the Catholic Church occupied a prominent place in the educational process in the country, especially in the school education of women. In these terms, a number of women's colleges were set up, destined for a refined formation marked by Christian Catholic values, and habits and practices aimed at the formation of the wife, mother and teacher. To these schools, society assigned responsibility for so-called "good training". In Goiás, as well as in other states, several congregations have worked in the educational field, among them, the Missionary Augustinian. Congregation founded in Spain in 1890, the Augustinian Missionaries came to Brazil, specifically to Catalão-GO, in 1921, with the purpose of assuming the education of children and young people. Subsequently, they spread to other regions. Considering that women should be more educated than educated, the present research highlights the training offered in this Catholic school: from language teaching to good manners, habits, manual skills, housewares inherent to women's assignments, be they at home or in the exercise of teaching profession. Thus, the study brings a discussion about ultramontane Catholicism; the Congregation of the Augustinian Missionaries, contemplating its action in the educational field, its objectives and practices; and about the college, its regulations, curriculum and pupil. The research is characterized as documentary.
"College of the nuns": female education in the normal course in the south of Goiás (1939-1968)
Keywords: Educação feminina; Educação católica; Curso normal; Feminine education; Catholic confessional school; Normal school; CIENCIAS HUMANAS::EDUCACAO